Respuesta :

gmany

[tex]The\ domain:\\m+3\neq0\ \wedge\ 3-m\neq0\\m\neq-3\ \wedge\ m\neq3\\\\\dfrac{3}{m+3}-\dfrac{m}{3-m}=\dfrac{m^2+9}{m^2-9}\\\\\dfrac{3}{m+3}-\dfrac{m}{-(m-3)}=\dfrac{m^2+9}{m^2-9}\\\\\dfrac{3}{m+3}+\dfrac{m}{m-3}=\dfrac{m^2+9}{m^2-9}\\\\\dfrac{3(m-3)}{(m+3)(m-3)}+\dfrac{m(m+3)}{(m+3)(m-3)}=\dfrac{m^2+9}{m^2-9}\\\\\dfrac{3m-9+m^2+3m}{m^2-9}=\dfrac{m^2+9}{m^2-9}\iff m^2+6m-9=m^2+9\ \ \ \ |-m^2\\\\6m-9=9\ \ \ \ |+9\\\\6m=18\ \ \ \ |:6\\\\\boxed{m=3\notin D}[/tex]

Answer: No solution

Answer:

3

Step-by-step explanation:

The given equation is ,

[tex]\implies \dfrac{ 3}{m+3} - \dfrac{ m}{ 3-m } =\dfrac{m^2+9}{m^2-9} [/tex]

Firstly lets try to simplify the LHS .Wr have ,

[tex]\implies \dfrac{ 3}{(3+m)(3-m)} =\dfrac{m^2+9}{m^2-9} \\\\\implies \dfrac{ 3(3-m)-m(m+3)}{ 3^2-m^2}= \dfrac{m^2+9}{m^2-9} [/tex]

Simplify using identity , we get ,

[tex]\implies \dfrac{ 9-3m -m^2-3m }{ 9-m^2} = \dfrac{m^2+9}{m^2-9} [/tex]

On futher simplyfing we will get a equation as ,

[tex]\implies m^2-6m +9= m^2 -9 \\\\\implies 6m = 18 \\\\\implies \underline{\underline{ x = 3 }}[/tex]

Hence the required answer is 3 .